2018
DOI: 10.1021/acsami.8b11527
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastretchable Multilayered Fiber with a Hollow-Monolith Structure for High-Performance Strain Sensor

Abstract: As a crucial component of data terminal acquisition devices, flexible strain sensor has shown promising applications in numerous fields, such as healthcare, bodynet, the intelligent traffic system, and the robotic system. For stretchable strain sensor, it remains a huge challenge to realize a fine balance of wide detection range and high sensitivity. Here, an electrically conductive carbon nanotube/thermoplastic polyurethane fiber with a multilayered, hollow, and monolith structure, accompanying high stretchab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 52 publications
0
69
0
Order By: Relevance
“…This is because high content of MWCNT caused serious agglomeration due to the strong Van der Waals force and limited the movement of SBS molecular chains. [ 19 ] Although SSCCSF‐13 has the lowest tensile strength and elongation at break, it is still within a reasonable level for stretchable strain sensors. [ 32,33 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because high content of MWCNT caused serious agglomeration due to the strong Van der Waals force and limited the movement of SBS molecular chains. [ 19 ] Although SSCCSF‐13 has the lowest tensile strength and elongation at break, it is still within a reasonable level for stretchable strain sensors. [ 32,33 ]…”
Section: Resultsmentioning
confidence: 99%
“…Microstructural design including multilayer structures and hollow‐monolith structures is considered as an effective method to obtain high‐performance strain sensor. [ 19,20 ] Among them, the core‐sheath structure with various performances in different layers have attracted widespread attention for fabricating flexible sensors in recent years. [ 21,22 ]…”
Section: Introductionmentioning
confidence: 99%
“…Durability is an another significant index for actual application of flexible strain sensors, as excellent durability can reduce the economic cost and increase popularity. [38][39][40] As shown in Figure 7c, the MCTF strain sensor shows significant stability and repeatability during 10 000 cycles (strain 50% at a rate of 100 mm min −1 ). The inset of Figure 7c presents several loadingunloading cycles (101-110, 5001-5010, 9001-9010 cycles) extracted from 10 000 cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Zhu et al reported finger‐monitoring sensors based on the conductive yarns with the deposited Pd nanoparticles, and the yarns have also been sewed into the gloves in the linear‐type. In another work, ultra‐stretchable polyurethane (PU)/carbon nanotubes composite filament with a hollow‐monolith structure have been utilized for strain sensing the physical movement, and the fiber bundles were directly bonded on the wrist, knee, or outside the T‐shirt as the functional bandage . All of these 1D fiber‐shape strain sensors, however, act as the independent devices or the accessories of clothes, still making some unsatisfactory, uncomfortable, and complicated sensing system, even cannot be named as “really” wearable devices.…”
Section: Introductionmentioning
confidence: 99%
“…In another work, ultra-stretchable polyurethane (PU)/carbon nanotubes composite filament with a hollow-monolith structure have been utilized for strain sensing the physical movement, and the fiber bundles were directly bonded on the wrist, knee, or outside the T-shirt as the functional bandage. [19] All of these 1D fiber-shape strain sensors, however, act as the independent devices or the accessories of clothes, still making some unsatisfactory, uncomfortable, and complicated sensing system, even cannot be named as "really" wearable devices. Thus, it is highly desirable to integrate sensors and clothes into one system, toward compact smart clothes with selfsensing performance.…”
Section: Introductionmentioning
confidence: 99%